Upaya Meningkatkan Motivasi Belajar Siswa Melalui Penerapan Model Pembelajaran Project Based Learning (PjBL) - Nurul Ainiyah; Arjudin Arjudin; Novianti Kaninta (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
The purpose of this research is to increase students' learning motivation by using the Project Based Learning Learning Model. This research was conducted for 2 cycles in class 3B with a total of 28 students. Research data was collected through a questionnaire that measures 4 elements of motivation, namely attention, relevance, confidence, and satisfaction (ARCS) through the Project Based Learning model. The results of class action research showed that in the first cycle the percentage of students who were motivated was 75%, and in the second cycle it increased to 89%. Thus it is concluded that the application of the Project Based Learning learning model can increase student motivation.